ANALISIS GOOD CORPORATE GOVERNANCE TERHADAP REAKSI PASAR PADA PERUSAHAAN PERTAMBANGAN LOGAM DAN MINERAL LAINNYA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nurdina, Nurdina; suhardiyah, martha (Universitas PGRI Adi Buana, 2017)
Issues regarding Corporate Governance began emerging, particularly in Indonesia in 1998, when Indonesia is experiencing a prolonged economic crisis. Many parties who said the length of the process improvements in Indonesia are caused by very weak Corporate Governance implemented in companies in Indonesia. Since that time, both the Government and investors are starting to give significant attention in the practice of Corporate Governance. The purpose of this study is to test any real effect the application of Good Corporate Governance as measured by the Board of Commissioners are independent, institutional ownership, Board of Directors, and the existence of the audit committee of the results of the reaction against the stock. The sample in this study are metals and minerals mining company that went public in his report which publishes the BEI and entered in the ranking of Corporate Governance Perception Index (CGPI) in 2011 – 2015. By using the method of multiple linear regression analysis showed that the independent variables, which are represented by the Board of Commissioners are independent, institutional ownership, Board of Directors, and the audit committee does not have an effect on the dependent variable that is market reaction. Keywords: Good Corporate Governance, market reaction